PERBEDAAN PENGETAHUAN LANSIA SEBELUM dan SESUDAH DIBERIKANPENYULUHANKESEHATAN TENTANGHIPERTENSIDI POSBINDU CEMARA PUSKESMASPAMULANGTAHUN 2016 - Ernida Dwi Jani V; Royani (STIKes IMC Bintaro, 2017)
Introduction. Hypertension is a condition where the systolic blood pressure ≥ 140 mmHg and diastolic blood pressure ≥ 90 mmHg on two occasions with an interval of five minutes at rest. Knowledge or cognitive domain is very important for the formation of a person's actions (overt behavior). Knowledge of health will affect the behavior of medium-term result (intermediate impact) of health education. Research Porpuse of this study was to determine differences in knowledge of the elderly before and after health education about hypertension in Puskesmas Posbindu Pamulang. Research methodology. This study research design Quasi Experimental approaches one group pretest and post-test. The population in this study are elderly aged ≥ 55 years with the inclusion and exclusion criteria specified. Research instrument used in the form of a questionnaire with a sample size of 25 people. The result of the research. Data were analyzed using the Normality of data and T-test. Based on t-test the results in this study were p value of 0.000. Conclusion. This means that thre are significant differences in the level of knowledge of the elderly. So it can be concluded that health education be helpful in improving the health education elderly knowledge about hypertension. Suggestions are expected to increase in the implementation of health education in the form of health education, especially the elderly so that people have enough knowledge about health.